Methodology of legal research in the security field - Huz Anatolii; Radovetska Liudmyla; Tykhomyrov Oleksandr; Tugharova Oksana; Shepeta Olena (2024)
The relevance of the study lies in the fact that in the context of armed aggression against Ukraine, the most scientifically relevant issues are those related to the security and defense sector, and the development of effective practical recommendations in this area is impossible without proper theoretical substantiation. The purpose of the study was to determine certain aspects of the use of methodological tools in conducting legal research in this area. To achieve its purpose and objectives, the author used general scientific and special research methods. The main results of the study are the argumentation of the position that at the present stage, the most reliable and objective legal knowledge should be considered that which involves the use of special methods, techniques and compliance with the principles of knowledge acquisition. Today, the system of legal sciences is gradually developing its own methodology based on the general scientific principles of knowledge; legal science forms it in close connection with and in accordance with the subject matter of research, reflecting the peculiarities of the object of study and its specifics. The security and defense sector, in turn, also requires a separate scientific approach and research tools, since the activities of the State in this sector, which are its exclusive prerogative, involve ensuring the sovereignty of the State, its independence in the international arena, and protection of the population on its territory. The conclusions of the study are that the system of legal sciences in Ukraine is gradually developing its own methodology in accordance with the peculiarities of the object under study and the area in which it realizes its tasks. The research is devoted to the study of an issue which is of topical importance both for the practical activities of state bodies performing functions in the security and defense sector and for further scientific research.